The MICROALBUMINURIA AS A POSSIBLE BIOMARKER IN EARLY DETECTION OF KIDNEY LESIONS IN PATIENTS WITH TYPE 2 DIABETES - Brezovska-Kavrakova, Julijana Marko; Bogdanska, Jasna; Cekovska, Svetlana; Topuzovska, Sonja; Labudovikj, Danica; Tosheska-Trajkovska, Katerina; Kostovska, Irena; Ampova, Hristina; Emin, Melda; Petkovska, Lidija; Ahmeti, Irfan (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Today, there is growing evidence supporting the association between renal failure and microalbumin (McA) concentration. The role of McA in the development of microcirculation damage in diabetic nephropathy (DN) has been proven. In our obsevational  study were including 78 patients with type2 diabetes. The baseline level of McA showed to be significantly increased in patients with DN, and it was related to the severity of the renal disease. We were focusing on patients with a five-year-old diagnosis of diabetes mellitus  type 2 (DM-2). After their a two-year follow-up, we found that microalbumin in urine  increased afther 6 mounths and one year in some of patients. Microalbumin  was  determined using of turbidimetric method in the laboratory of the Institute of Medical and Experimental Biochemistry. For serum creatinine, we were using a standardized enzyme method. MDRD4 formula was the best  for calculation of glomerular filtration rate. A statistical analysis of the data was performed with the statistical program IBM SPSS 26 for Windows. The results obtained regarding albumin in urine showed: mean 42.04 mg/L, extremely high CV, and were in negative correlation with GFR. Using a multivariate linear regression model, we proved the fact that the increased McA level in the urine significantly influenced the decline of GFR. In patients with a high risk of developing diabetic nephropathy, appropriate measures were taken in order to register and prevent the disease on time. The large variability could be due to differences in disease progression among individuals since microalbuminuria is a marker of early kidney damage, besides other promoters of progression. Keywords: microalbuminuria, glomerular filtration rate, MDRD formula.